A detailed mechanistic investigation into the reaction of 3‐methylpentanoic acid with Meldrum's acid utilizing online NMR spectroscopy. (31st August 2015) - Dunn, Anna L.; Codina, Anna; Foley, David A.; Marquez, Brian L.; Zell, Mark T.
Abstract : A thorough investigation into the mechanism of the reaction of 3‐methylpentanoic acid and Meldrum's acid using online NMR spectroscopy is reported. This study is an expansion of a previous analysis of this chemical transformation in the synthesis of an active pharmaceutical ingredient imagabalin. The 3‐methylpentanoic acid analogue reveals similar behavior under the reaction conditions. Online NMR spectroscopy and offline characterization experiments reveal new information about the mechanism, providing conclusive spectroscopic evidence for the previously hypothesized dimer anhydride intermediate species 3‐methylpentanoic anhydride as a productive intermediate. The presence of an acyl chloride intermediate species, 3‐methylpentanoyl chloride, is also revealed for the first time in this synthesis. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A thorough investigation into the mechanism of the reaction of 3‐methylpentanoic acid and Meldrum's acid using online NMR spectroscopy is reported. Structural characterization of a number of reaction species is presented, providing evidence of the productive intermediates to product formation.